Antimicrobial photodynamic therapy minimizes the deleterious effect of nicotine in female rats with induced periodontitis. Issue 1 (January 2016) - Gualberto, Erivan; Theodoro, Letícia; Longo, Mariellén; Novaes, Vivian; Nagata, Maria; Ervolino, Edilson; Garcia, Valdir
Abstract The aim of this study was to compare the use of antimicrobial photodynamic therapy (aPDT) as an adjunct to scaling and root planing (SRP) in the treatment of experimentally induced periodontitis in female rats that were systemically treated with or without nicotine. Female rats (n = 180) were divided into two groups: vehicle administration (Veh) and nicotine administration (Nic). Mini-pumps containing either vehicle or nicotine were implanted in the rats 30 days before the induction of experimental periodontitis (EP). EP was induced by placing a cotton ligature around the left mandibular first molar. After 7 days, the ligature was removed, and the rats were randomly divided into three treatment subgroups: SRP (only SRP), DL (SRP plus diode laser), and aPDT (SRP plus aPDT). The aPDT consisted of phenothiazine photosensitizer deposition followed by diode laser irradiation. Ten rats from each subgroup were euthanized at 7, 15, and 30 days after treatment. Alveolar bone loss (ABL) in the furcation region was evaluated using histological, histometric, and immunohistochemical analyses. The rats that were treated with nicotine showed more ABL compared to those treated with vehicle. In both the Veh and Nic groups, SRP plus aPDT treatment resulted in reduced ABL, smaller numbers of both TRAP- and RANKL-positive cells, and higher numbers of PCNA-positive cells compared to SRP treatment alone. aPDT was an effective adjunctive therapy for the treatment of periodontitis in female rats regardless of whether they received nicotine.